Sensory motor activities for early development : a practical resource - Hong, Chia Swee; Rumford, Heidi (London ; New York : Routledge, Taylor & Francis Group, 2020)
'Sensory motor activities are crucial for children to learn from their environment. Bridging the gap between theory and practice, this revised edition is a complete package of tried-and-tested sensory motor activities for children, covering basic movements, interoception, sensory and body awareness and early visual perceptual skills'--
Working with the child, parents/carers and practitioners -- Introducing the sensory systems and interoception -- Stimulating sensory and body awareness -- Encouraging basic movement -- Promoting hand skills -- Encouraging spatial and early visual perceptual skills -- Working in groups -- Using creative activities.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
OCLC control number change
Keywords: Perceptual-motor learning; Sensory stimulation; Motor ability in children; Developmentally disabled children; EDUCATION -- Teaching Methods & Materials -- General; Developmentally disabled children; Motor ability in children; Perceptual-motor learning; Sensory stimulation